Development of Creative Reading Teaching Materials for Fable Texts Using the Powtoon Application for Grade VII Students - Wikaningtyas Fitriati Yuwana (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to develop creative reading teaching materials using the Powtoon Application in class VII learning and to see the usability and feasibility of creative reading teaching materials for students. The research method used in this study is the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluations) development model. Data were collected by observation, interviews and questionnaires. Data analysis was carried out using qualitative and quantitative descriptive data analysis. Product feasibility testing was carried out by one material expert and one media expert, as well as 3 Indonesian language teacher respondents and 45 class VII students, namely SMPN 28 Jakarta, SMPN 7 Tambun Selatan, and SMPN 5 Tambun Utara. The results of the study showed that the material presented in the form of creative reading teaching materials in audiovisual form using the Powtoon application can be used by teachers and class VII students and can be accessed using gadgets or computer devices. The quality of creative reading teaching materials using the Powtoon application in learning fable texts received an assessment in the very good category, the assessment from material experts got an average score of 91%, while the assessment from media experts got an average score of 91%. Furthermore, the assessment of Indonesian language teachers got an average score of 95% and the assessment of students got an average score of 97%. Based on this assessment, it is concluded that the creative reading teaching materials using the Powtoon application in learning fable texts for class VII that have been developed are declared suitable for use in learning.